Optimization in structural altitude for seismic base isolation at medium risk earthquake disaster region - Islam, A.B.M.S.; Jameel, Mohammed; Jumaat, Mohd Zamin; Rahman, M.M. (2013)
Seismic isolation through rubber bearing at structural base poses significant reduction in energy ensuring flexibility to the structure. The bearings act as earthquake induced load resisting system. This seismic load is predominant lateral load acting on building structures along with wind load. If wind load is much greater than the earthquake load, inserting isolator will bring no advantage in design. Furthermore, if the time period of a building without isolator is greater than the reasonable value, incorporation of isolator will not convey much difference to the building behavior with respect to seismic load. So the objective of the study is to examine the building structures in region of medium risk seismicity for dissimilar heights and plan area to predict critical height up to which energy dissipation bearing is competent. 108 numbers of models for different configurations of 4 to 30 stories structures have been built up. All the structures are analyzed in finite element approach subjected to proper lateral loading. The characteristics and functions of different kinds of isolators are introduced along with isolation suitability for building structures. The relationship among governing lateral load, building altitude and time period is evaluated as well. The study reveals that though seismic base shear governs up to larger building height, for higher tallness, the structure may experience larger time periods than the most suitably limiting value for incorporating isolator. Realistic structural analyses envisage that up to 30 similar to 40m height seismic base isolator can be efficiently incorporated in medium risk seismic vicinity for RCC building structures.